GENDER DIFFERENCE IN AWARENESS AND BEHAVIOURS OF MEDICAL AND DENTAL STUDENTS ABOUT CORONA VIRUS DISEASE (COVID-19) IN PAKISTAN - Lodhi, Fahad Saqib; Rabbani, Unaib; Khan, Adeel Ahmed; Abrar, Saidul; Laraib, Ayesha; Irum, Saadia (Journal of Ayub Medical College Abbottabad, 2022)
Background: Medical and dental students are the future of health workforce and a potential volunteer pool in the COVID-19 crises. This study aimed to assess the level and gender differences in the awareness, attitude and behaviours of medical and dentals students about COVID-19 in Pakistan. Methods: An online cross-sectional survey was conducted among medical and dental undergraduate students in Khyber Pakhtunkhwa province. Data was collected using a structured questionnaire having four sections: socio-demographics, knowledge, attitude and practices. Results: A total of 1770 medical and dental students participated and completed the questionnaire. About 1239 (70%) of the respondents were female and 1526 (87%) were MBBS students. We found that 1685 (95%) of the students had adequate knowledge. Majority, 1565 (89%) of the students was concerned about COVID-19 and 1480 (84%) believed that disease will ultimately be controlled. Only about 1129 (64%) of the participants in our study had adequate practices. Male gender was associated with higher risk of inadequate practices. Conclusion: There were good knowledge and attitudes about COVID-19 among medical and dental students. However, one third of the participants did not have adequate practices and female had better practices than male students. This gap in the knowledge and practice calls for urgent interventions to improve practices.